Study of the dynamic performance of an Otto engine using mixtures two types of “Extra and Super” gasolines - Guzmán, Alex Rodolfo; Cueva, Eduardo; Peralvo, Alexander; Revelo, Milton; Armas, Alexis (Enfoque UTE, 2018)
The purpose of this study is to compare and examine the performance of an engine, using gasoline with 92 octanes (Super), 87 octanes (Extra) and two volume mixtures of these two types of gasoline, the first one had 50% of volume of each type, the second one had a volume value of 70% of Super with 30% of Extra. To evaluate the performance of the engine, a dynamometer was used to obtain the characteristics curves of power and torque, a gas analyzer was used to determine the level of emission of pollutant gases from the engine (CO, CO2, HC, y NOx), finally an homologated cycle was carried out to measure fuel consumption. The mixture of Super 50% with Extra 50% obtained a higher power value with 81.3 HP, the Super gasoline obtained a higher torque value of 89.2 lb-ft, in cycle ASM 2525, the CO, HC and NOx were measured, the Super gasoline, Extra gasoline and the mixture of 50% of each gasoline were the least polluting ones, in cycle ASM 5015, CO, HC and NOx were measured, Super gasoline, Extra and the Super 70% V mixture with Extra 30% V respectively were less polluting, in the static gas test the least polluting was Super.